La plus secrète mémoire des hommes de Mohammed Mbougar Sarr. Apories et paradoxes - Hanae Abdelouahed (Multilinguales)
Crowned with the Prix Goncourt 2021, the novel by Senegalese writer Mohammed Mbougar Sarr, La plus secrète mémoire des hommes has been praised by several readers and critics. The singularity of the work is manifested in the writing techniques chosen by the author that can be considered a predictor of success. In this regard, the apology of transgression is deployed in the subversion of clichés and stereotypes that ghettoize the black francophone writer. This study therefore attempts to show how the questioning of history in its phenomenology reveals a decentered vision of the author and attempts to explore all the determinants that make the creation of an African author as abundant as it is complex a subject of paradox.